Ocorrência de fungos negros em ambientes domésticos - Melati, Ranieri Bueno [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Black fungi are able to adapt to extreme environmental conditions, such as: high temperatures, the presence of toxic chemical substances and lack of nutrients. Besides, they are also potential pathogens to humans. The natural environment of many black fungi is still unknown and some studies are being conducted to evaluate the biodiversity of this group and their different habitats. This study aimed to isolate black fungi in domestic environments and facilities, such as toothbrushes, fridge sealing rubbers, bathroom strainers and divisions, windows, wall tiles and bath sponge. For the collection, material surfaces were scratched with a scalpel and the resulting fragments were sewed in Mycosel agar (DifcoTM), supplemented with actidione to inhibit the growth of highly-sporulating fungi. Plates were incubated at 25ºC for three weeks. The 46 isolated fungi were maintained on MA2% slants at 8ºC and cryopreserved at -80ºC. Fungal identification was performed through the analysis of macro and microscopic features and ITS rDNA sequencing. The following black fungi taxa were found: Ascomycota sp., Cladosporium spp., Dothideomycete sp., Exophiala alcalophila, Ochroconis mirabilis and Rhinocladiella atrovirens. Non-melanized fungi were also found, such as Geosmithia sp., Penicillium sp. and Rhodotorula mucilaginosa. The temperature tests showed that isolated black fungi were not able to grow at 37°C, however, this temperature proved to be fungistatic to 43% of them. According to literature, all black fungi isolated in this study are opportunistic pathogens and additional studies are necessary to evaluate the risk that these micro-organisms offer to health, once they were isolated from domestic environments

Os fungos negros podem se adaptar a condições ambientais extremas, tais como: altas temperaturas, presença de substâncias químicas tóxicas e escassez de nutrientes. Além disso, são também patógenos oportunistas para os humanos. O ambiente natural de muitos fungos negros ainda é desconhecido e alguns estudos estão sendo realizados para avaliar a biodiversidade deste grupo e seus diferentes habitats. Este estudo teve como objetivo isolar fungos negros em ambientes e utensílios domésticos, tais como escova dental, borracha de vedação de geladeiras, ralos e boxes de banheiros, janelas, azulejos e esponjas de banho. Para as coletas, as superfícies dos materiais foram raspadas e os fragmentos resultantes foram semeados em ágar Mycosel (Difco™), suplementado com actidiona para inibir o crescimento de fungos altamente esporulantes. As placas foram incubadas a 25°C por aproximadamente três semanas. Os 46 fungos isolados foram preservados em tubos inclinados com MA2% mantidos a 8°C e por ultracongelamento a -80°C. A identificação dos fungos foi realizada através de análises macro e microscópicas das colônias e seqüenciamento da região ITS do rDNA. Os seguintes táxons de fungos negros foram encontrados: Ascomycota sp., Cladosporium spp., Dothideomycete sp., Exophiala alcalophila, Ochroconis mirabilis e Rhinocladiella atrovirens. Fungos hialinos também foram isolados, como Geosmithia sp., Penicillium sp. e Rhodotorula mucilaginosa. Os testes de temperatura mostraram que os fungos negros isolados não cresceram a 37ºC; no entanto, esta temperatura foi fungistática para 43% dos mesmos. De acordo com a literatura, todos os fungos negros obtidos no presente estudo são patógenos oportunistas e estudos adicionais são necessários para avaliar o risco que estes micro-organismos oferecem à saúde, uma vez que foram isolados de ambientes domésticos
Keywords: Fungos; Fungos - Culturas e meios de cultura; Morfologia (Biologia)